The complete chloroplast genome sequence of a traditional Chinese medicine plant Bulbophyllum disciflorum Rolfe (Orchidaceae). Issue 1 (2nd January 2020) - Tang, Yang; Yang, Jiapeng; Niu, Zhitao; Ding, Xiaoyu
Abstract: Bulbophyllum disciflorum is one of Orchidaceae species, which has important ornamental and economic value. Here, we reported the first chloroplast genome sequence of Bulbophyllum . The genome of B. disciflorum is 148, 554 bp in length, including a large single-copy (LSC) of 79, 001 bp, a small single-copy (SSC) of 16, 797 bp, and a pair of inverted repeat regions (IRa and IRb ) of 26, 378bp. It contains 108 unique genes consisting of 74 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The phylogenetic analysis revealed that Bulbophyllum is sister to the genus of Dendrobium .